Future Trends Research for Holistic Education with a “Sekolah Penggerak” Model - Punuh, Liesje Grace Lourino; Tambingon, Henny Nikolin; Rawis, Joulanda A.M; Mangantes, Meisie Lenny (International Journal of Information Technology and Education, 2022)
This study discusses Holistic Education with a Sekolah Penggerak and examines the current state of research. These findings will provide insight for further research and experimental opportunities aligned with Holistic Education with a Sekolah Penggerak. Many data, models and innovations regarding Holistic Education with a Sekolah Penggerak have been published in different and complex ways. This has explained the overall picture of Holistic Education with a Sekolah Penggerak. This study aims to analyze and identify data sets, research trends, and methods that have been used since 2010. We used a systematic literature review method. We carry out the process of identifying, assessing and interpreting research evidence and reviewing the literature to answer specific research questions. We analyzed by selecting the main study in Holistic Education with a Sekolah Penggerak. We have mapped trends, datasets, and methods in Holistic Education with a Sekolah Penggerak that has been implemented. This study concludes that we have successfully identified and analyzed research trends in Holistic Education with a School of Mobilization measurably and systematically in the last 12 years.